G360 A cytokine storm is brewing. (7th April 2014) - Long, M; Al-Obaidi, M; Hawley, D; Shackley, F; Waruiru, C; Tattersall, R; McMahon, A
Abstract : Background: Haemophagocytic lymphohistiocytosis (HLH) is a severe systemic inflammatory condition caused by dysregulation in Natural Killer T cell function. This results in excessive activation and proliferation of lymphocytes and histiocytes which results in a "cytokine storm" and uncontrolled haemophagocytosis. HLH should be considered in cases of unexplained unremitting fevers, sudden onset of cytopaenias, liver dysfunction and clotting abnormalities. It can be associated with rashes, hepatomegaly, splenomegaly and central nervous system symptoms (headache, lethargy, irritability, seizures, coma). Due to the non specific nature of presentation, HLH can often be overlooked, even when patients are extremely unwell. Traditionally, HLH is divided into primary HLH (genetic cause identified), and secondary HLH, which is associated with a variety of conditions (neoplasic, infectious and autoimmune). In autoimmune disease HLH is usually referred to as macrophage activation syndrome (MAS). HLH can be difficult to diagnose and early recognition and prompt treatment is essential to prevent the significant mortality associated with this disorder. Aims: To raise awareness of HLH, to outline the complexity of this disorder and the challenges that exist in diagnosis. Methods: We present three cases of HLH seen at a tertiary paediatric hospital with a tertiary paediatric rheumatology unit between January and October 2013. In two cases there was MAS associated with systemic juvenile idiopathic arthritis. In one case the diagnosis is likely to be a primary HLH. We outline the presentation and course of the illness and the results of investigations. Results (Image 1): one and two were successfully treated with methylprednisolone and Anakinra (Interleukin – 1 blocker). Patient three initially responded to methylprednisolone however, subsequently eventually required treatment with dexamethosone and cyclosporine HLH protocol. Conclusion: HLH or MAS, regardless of terminology preferred, needs prompt recognition and treatment to prevent fatality. We present this series of cases to highlight the complexities and challenges of diagnosis of this condition. It is essential to raise awareness of this condition amongst paediatricians and furthermore to stimulate the development of guidelines that encompass the diagnosis and management of primary and secondary HLH.